Tax Avoidance Jangka Panjang di Indonesia - Herlan Herlan; Tryas Chasbiandani (Postgraduate Program Merdeka University, 2019)
Long run tax avoidance is a method by Dyreng et al (2008), which can show the real tax avoidance activity by the firms. The research aims to analyze long-run tax avoidance in Indonesia, for the factor that influences long-run tax avoidance and the effect of tax avoidance on firm value. The research was conducted for nonbanking and financial firms in Indonesia Stock Exchange for the period 2015-2016. The analytical used is the fixed-effect method. The result of this research indicates that short-run tax avoidance has a positive influence on long-run tax avoidance. The sample of this research, the short-run tax avoidance is persisted over a period. DOI: https://doi.org/10.26905/afr.v2i1.3171